2018
DOI: 10.15561/18189172.2018.0107
|View full text |Cite
|
Sign up to set email alerts
|

Gaming technologies in the development of spine flexibility and the coordination of children and teenagers' movements in sports classes in country health camps

Abstract: to investigate the impact of gaming technology on the development of spine flexibility and movement coordination in children and teenagers. Material: the study involved children and teenagers (n = 670, age 8-12 years). The duration of the study was 2 shifts (21 days each) in a country recreation camp. There were conducted 42 lessons. In the first shift, schoolchildren (n = 330, control group) were engaged in the program of physical education of additional education. The basis of the program were the following … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 11 publications
0
3
0
1
Order By: Relevance
“…Researchers experimentally substantiate the improvement of physical fitness indicators of students of technical and engineering areas, conducted using an innovative enhanced coordination mode [13]. Studies show that already after the first course, students engaged in active motor activity are significantly ahead of their peers who participate in the regular program in terms of their agility characteristics in the implementation of various motor actions [7,21]. Only the implementation of a system of educational and extracurricular physical culture and sports activities can enhance the effect of positive physical adaptation to the vocational training of students in higher education [14].…”
Section: Discussionmentioning
confidence: 99%
“…Researchers experimentally substantiate the improvement of physical fitness indicators of students of technical and engineering areas, conducted using an innovative enhanced coordination mode [13]. Studies show that already after the first course, students engaged in active motor activity are significantly ahead of their peers who participate in the regular program in terms of their agility characteristics in the implementation of various motor actions [7,21]. Only the implementation of a system of educational and extracurricular physical culture and sports activities can enhance the effect of positive physical adaptation to the vocational training of students in higher education [14].…”
Section: Discussionmentioning
confidence: 99%
“…• Agricola et al (2015), Palomo-Nieto et al (2015 on the importance of movement coordination of different parts of the body in evaluating children's and adolescents' coordination abilities; • Volkov, and Nagovitsyn (2018) about the influence of motor activity and purposeful usage of physical education means on a positive dynamics of movement coordination development in children and adolescents; • Meadmore, Exell, Burridge, Hughes, Freeman, and Benson (2018) on the gender differences in children related to the body composition and movement coordination. During the analysis, the study confirmed Ivashchenko's (2016) conclusions as to the usage of factor analysis for the evaluation of the current state of motor preparedness, and the usage of discriminant analysis for the evaluation of the state dynamics in the age range, which makes it possible to determine informative indicators for a comprehensive control of motor preparedness.…”
Section: Discussionmentioning
confidence: 99%
“…Perempuan diidentikan dengan makhluk lemah yang tidak diberikan kebebassan untuk mengekplorasi lingkungan dan alam karena dianggap akan membahayakan mereka. Kebanyakan orang tua yang memiliki anak perempuan lebih senang memberikan anak mereka mainan seperti boneka dan hal-hal yang akan menunjang peran mereka dimasyarakat nanti (Gonzalez et al, 2016;Volkov & Nagovitsyn, 2018). Hal ini menyebabkan kebanyakan anak perempuan malah mengalami keterlambatan perkembangan gerak dasar maupun koordinasi gerak mereka.…”
Section: Hasil Dan Pembahasanunclassified